Analysis Analysis of the Influence of Economic Growth, Domestic Investment, and Open Unemployment Rate on Regional Inequality in Indonesia - Sihite, Anggun; Nurjannah; Rinaldi Syahputra (Jurnal Samudra Ekonomika, 2025)
Inequality is one of the obstacles to economic development in every country. This makes economic growth centered only in certain areas so that people experience differences in economic opportunities and access to infrastructure. This study is intended to look at the influence of economic growth, domestic investment and open unemployment rate on regional inequality in Indonesia. The object of this research is 34 provinces in Indonesia. This research is in the form of quantitative research using the panel data regression method. Data processing with E-views software 12. From the research conducted, the results of Economic Growth have a positive and insignificant effect on regional inequality with a probability value of 0.7814. The domestic investment variable has a negative and significant effect on regional inequality with a probability value of 0.0000. The variable Open Unemployment Rate has a positive and insignificant effect on regional inequality with a probability value of 0.3393. Simultaneously, Economic Growth, Domestic Investment, and the Open Unemployment Rate have a significant effect on regional inequality and the three variables studied have a contribution of 77.6336% and the rest are explained by other variables outside this study.